Adolescent Health: Changing Over Time in Nepal - Pokhrel, Umakanta (Asian Journal of Population Sciences, 2022)
This article aims to analyse the adolescent health with changing context of demography, access and use of family planning methods and reproductive health and national policies adopted by the Nepalese government. Adolescent is complex transitional phase and equally vulnerable too due to its tender nature, furthermore advancement of technology from local level to global level challenges to adulthood greater today than ever before where they are natured throughout traditional norms, values and practices. Reports of census and periodical national level surveys show some improvement on sexual and reproductive health as a whole but in terms of bridging gap between disparities still remains significant. Though, following the guidelines of international conferences for universal excess quality reproductive health services to all it is poor to address the issues of adolescent. To meet the mandates of Nepal’s policies and programmes need a broad understanding of the sexual and reproductive health as it is lower level of information in terms of places to obtain safe abortion. Adolescent has more aware about ANC and PNC but unmet need for contraception is higher than other age groups. After conditional legalization of abortion maternal mortality has decreased but still high. In contrast of government efforts to enhance CPR, it is constant over few last years. Early marriage is common in society in contrast of legal provision of lower age of marriage. Age at marriage is the most attributing factors to early sexual debut among Nepalese women. The trend of adolescent pregnancy seems to be decreasing but still exists as a great challenge to meet the target set by government.